Insect in vitro System for Toxicology Studies — Current and Future Perspectives - Cc, Sheeja; Arun, Damodaran; Divya, Lekha (Frontiers in Toxicology, 2021)
In vitro cell culture practices are valuable techniques to understand the mechanisms behind vital in vivo biological processes. In vitro cells have helped us to attain a deeper understanding of functions and mechanisms conserved in the course of evolution. Toxicology studies are inevitable in drug discovery, pesticide development, and many other fields that directly interact with human beings. The proper involvement and regulatory steps that have been taken by animal ethical societies in different parts of the world resulted in the reduced in vivo use of mammals in toxicological studies. Nevertheless, experimental animals are being killed where no replacement is available. Reduction in the use of in vivo mammalian systems is achieved by using the in vitro mammalian systems. Invertebrates like insects can be a better alternative to the vertebrate models.